REVIEW OF PLANNING THEORY OF NUMBER OF EMPLOYEES OF FREIGHT MOTOR COMPANY - L. S. Trofimova; K. A. Barabaevna (Вестник СибАДИ, 2017)
The article presents the results of the analysis, which allowed the weary twist that previously developed techniques were aimed at planning exponents-lam reached in the previous period, as well as inflow and outflow of rolling stock in accordance with the previously existing system of policy-pla-ning. Application of the rules, regulations and the fund of working time without taking into account the impact of technical and operating characteristics of the planning results do not take into account the peculiarities of the practice-cargo traffic at the relationship of commercial and tech-tion operation. The necessity of creating a number of methods of planning of employees, taking into account the peculiarities of the operation of motor transport enterprise.